Design of embedded system of volleyball training assistant decision support based on association rules - Xu, W.; Liu, F. (Microprocessors and Microsystems, 2021)
Volleyball generally determined by two judges and two lines hosted. In the first volleyball net official referees in the table is positioned at the opposite side of the raised platform. The first referee does not move around, but they need to stand for long periods, usually 45 min to two hours, depending on the length of the game, while maintaining a high level of focus and alertness. The second referee assists and stood first referee make a call, primarily focused on network play across the floor. Volleyball is a fast-moving, the area contains. Therefore, it is possible to follow the action visually, look at the small details are very important. Volleyball officials must always stay alert and focused during playback, so as not to miss a beat. Ref 12 feet along a second transfer region and a first edge opposite the lateral movement of the referee and the ball game. The judge of the production line stood on the opposite corner throughout the game, and the contact with the in and out call to assist the first referee and search for the ball on the net blocked. Judges need excellent eyesight, good judgment and agility, move up and down the sideline to get the ball and avoid collisions with the best perspective of the player.